Development of E-Book Containing The Values of Local Wisdom Of Bali In Social Science Lesson Grade IV Elementary School - Dewi, Ni Kadek Rosita; Agung, Anak Agung Gede (International Journal of Elementary Education, 2021)
This research was conducted based on the results of the analysis of the learning media needs in elementary school. Teachers are less utilizing innovative learning media during online learning and the lack of strengthening local wisdom values in the era of globalization. The media being developed is an E-Book with the values of Balinese local wisdom. Â Therefore, this study aims to describe the process of designing an E-Book containing Balinese local wisdom values and knowing the results of E-Book validation according to expert reviews, individual trials, and small group trials. This type of research was a Â development research using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The data were collected by using questionnaire method with data analysis techniques, namely quantitative descriptive analysis. The results of the E-Book media validation based on the expert's assessment of the content of social subject obtained a score of 87.50% with good qualifications, instructional design experts obtained a score of 100% with very good qualifications, learning media experts obtained a score of 92.50% with very good qualifications. The results of the individual user test on 3 students obtained a score of 93.33% with very good qualifications, and the results of the user test through a small group test on 12 students obtained a score of 94.16% with very good qualifications. Based on the results of the product trial data analysis by experts and the results of user subject trials (students), it can be concluded that the E-Book media containing the values of Balinese local wisdom was suitable for learning social content in Grade IV of Elementary School. The implication of developing this E-Book required supporting facilities such as internet access, computers/laptops, cellphones, and the ability of teachers or students to access the E-Book.